Visual Outcome of Intravitreal Bevacizumab in Treatment of Diabetic Retinopathy - Kanwal Zareen Abbasi, Warda Ali, Qamar Farooq, Ali Raza, Ana Rizvi (Journal of Rawalpindi Medical College, 2018)
Background :To evaluate the efficacy of monthly intravitreal bevacizumab injections (1.25 mg/.05 ml) in improving or stabilizing visual acuity measured by Snellen’s visual acuity charts for diabetic retinopathy. Methods: This was a prospective Quasi experimental study of 59 diabetic patients having diabetic retinopathy with indication of intravitreal anti VEGF,Bevacizumab. Patients diagnosed of having fresh vitreous haemorrhage and diabetic macular edema were included. Maximum three intravitreal bevacizumab injections were given, each with a dose of 1.25mg in 0.05ml(at 0month, 1 month, 2 months) with final follow up at the period of 3 months. The criteria for improvement was a gain of at least one line on Snellen’s visual acuity chart, compared to the baseline while stabilization was considered if the visual acuity was unchanged relative to the baseline. Results: A total of 59 patients, 25 (49.1%) males and 34 (50.84%) females , having age range 40-65 years,were given intravitreal injection. Twenty six eyes (44.06%) with diabetic macular edema showed improvement while visual acuity was stabilized in 4 eyes (6.7%). In patient with vitreous hemorrhage, 27 eyes (45.76%) showed improvement while stabilization of visual acuity was noted in 2 eyes (3.3%). No patient with worsening of visual acuity was noted. Conclusion: Intravitreal Bevacizumab is very effective in improving the visual outcome in diabetic patients having macular edema and vitreous hemorrhage